THE LEADERSHIP OF THE MADRASA PRINCIPAL IN ENHANCING LEARNING QUALITY AMIDST COVID-19 PANDEMIC IN CENTRAL ACEH REGENCY - Mizal, Basidin; Tathahira, Tathahira; Basith, Rayhan Izzati (Jurnal As-Salam, 2024)
The role of the madrasa principal is pivotal in an educational institution. The leadership of the madrasa head determines the direction and is the main indicator of student achievement and achievements. Maintaining and improving the quality of education is one of the goals of national education, and madrasa heads are mandated to make it happen. The quality of learning in Indonesia is still a concern and is far from satisfactory. The COVID-19 pandemic is a scourge for education actors, especially school and madrasa principals, who are leaders in educational institutions to maintain the quality of learning. This research aims to determine the problems, strategies, and implications experienced by madrasa heads in efforts to maintain or improve the quality of learning during the COVID-19 pandemic. This research is classified as qualitative research using a descriptive analysis approach. This research involved madrasa heads in Central Aceh Regency. Based on the results of interviews, it was found that the biggest problem faced by madrasa heads during the pandemic was the lack of readiness of teachers and students to carry out distance learning from home. This readiness includes limited internet networks for students to access online learning media. In general, the strategy adopted by madrasa principals is to implement shift classes and involve the homeroom teacher in providing materials (printouts) and collecting assignments at school. All of this has implications for the role of madrasa heads, who must further increase the level of preparedness, decision-making, application of creative ideas, and risk management to the demands of educational development or emergencies.